The concept of person in Mounier's philosophy: convergences with orthodox theology - Apintiliesei, Ciprian Costin (Journal for the study of religions and ideologies, 2018)
As a representative of French personalism in the twentieth century, Emmanuel Mounier can be an interlocutor for the orthodox theology of the person, especially given the fact that he does not hide the Christian sources of his philosophy. The present article identifies his main lines of thought on the concept of person, namely the three dimensions: incarnation, communion and vocation. The incarnational dimension expresses the link of person with the material world and manifests itself in the person's commitment to society. The communitarian dimension expresses the constitutive relationship of the person with mankind, with all other human persons, and reveals itself in the constant effort of dispossession and abnegation in favour of others. The vocational dimension manifests, for its part, the indelible connection of person with God, and its expression is the act of meditation and interiorization. These are the dimensions that reflect a dynamic structure of person. The article then tries to formulate an answer to the questions: can one perceive a certain compatibility or affinity between his thought and the orthodox view of the person? If so, what would it be? For this purpose, Mounier's vision is succinctly confronted with three orthodox theologians of the twentieth century: the Russian theologian V. Lossky, the Romanian theologian D. Staniloae and the Greek metropolitan I. Zizioulas.